Hydrogels For Peptide Hormones Delivery: Therapeutic And Tissue Engineering Applications - Doostmohammadi, Mohsen (Drug Des Devel Ther, 2019)
Peptides are the most abundant biological compounds in the cells that act as enzymes, hormones, structural element, and antibodies. Mostly, peptides have problems to move across the cells because of their size and poor cellular penetration. Therefore, a carrier that could transfer peptides into cells is ideal and would be effective for disease treatment. Until now, plenty of polymers, e.g., polysaccharides, polypeptides, and lipids were used in drug delivery. Hydrogels made from polysaccharides showed significant development in targeted delivery of peptide hormones because of their natural characteristics such as networks, pore sizes, sustainability, and response to external stimuli. The main aim of the present review was therefore, to gather the important usages of the hydrogels as a carrier in peptide hormone delivery and their application in tissue engineering and regenerative medicine.